Safety update on the use of recombinant activated factor VII in approved indications. (June 2015) - Neufeld, Ellis J; Négrier, Claude; Arkhammar, Per; el Fegoun, Soraya Benchikh; Simonsen, Mette Duelund; Rosholm, Anders; Seremetis, Stephanie
Abstract: This updated safety review summarises the large body of safety data available on the use of recombinant activated factor VII (rFVIIa) in approved indications: haemophilia with inhibitors, congenital factor VII (FVII) deficiency, acquired haemophilia and Glanzmann's thrombasthenia. Accumulated data up to 31 December 2013 from clinical trials as well as post-marketing data (registries, literature reports and spontaneous reports) were included. Overall, rFVIIa has shown a consistently favourable safety profile, with no unexpected safety concerns, in all approved indications. No confirmed cases of neutralising antibodies against rFVIIa have been reported in patients with congenital haemophilia, acquired haemophilia or Glanzmann's thrombasthenia. The favourable safety profile of rFVIIa can be attributed to the recombinant nature of rFVIIa and its localised mechanism of action at the site of vascular injury. Recombinant FVIIa activates factor X directly on the surface of activated platelets, which are present only at the site of injury, meaning that systemic activation of coagulation is avoided and the risk of thrombotic events (TEs) thus reduced. Nonetheless, close monitoring for signs and symptoms of TE is warranted in all patients treated with any pro-haemostatic agent, including rFVIIa, especially the elderly and any other patients with concomitant conditions and/or predisposing risk factors to thrombosis.